Chemical Composition and Preservative Effect of Turkish Propolis on Egg Quality Durig Storage - SAHINLER, NURAY; GUL, AZIZ; COPUR, GULSEN (Asian Journal of Chemistry, 2010)
The present study was carried out to investigate chemical composition and preservative effects of Turkish propolis on quality of fresh eggs. For this purpose, different concentrations of ethonolic extract of propolis (5, 8, 10 % EEP) were prepared. Total of (9 period × 5 group × 10 n) 450 egg were used during experiment. The eggs were randomly divided into 5 experimental groups. The first, second and third group eggs covered with 5, 8, 10 % EEP, fourth group with alcohol control and fifth group as a control (uncovered), respectively. Ten eggs in each group were drawn randomly and examined each week between 17 March-12 May 2006. Chemical analysis of propolis extracts indicated that the propolis samples had high concentrations of the aromatic acids, esters and other derivatives which are responsible for the antibacterial, antifungal, antiviral, antiinflammatory and anticancer properties of propolis such as benzyl cinnamate, methyl cinnamate, caffeic acid, cinnamyl cinnamate and cinnamoylglcine besides the most common compounds as fatty acid, terpenoids, esters, alcohols hydrocarbons and aromatic acids. It was found that ethanolic extract of propolis improved interior egg quality.